Penyuluhan Tentang Pemanfaatan Sambiloto (Andrgraphis paniculata) Untuk Mencegah dan Mengobati Penyakit Hipertensi - Siti Rahmah Kurnia Ramdan; Marlina Indriastuti; Anna L Yusuf; Davit Nugraha; Panji Wahlanto (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: Hypertension is one of the factors causing cardiovascular disease and is the main cause of death in the world. Hypertension can be influenced by various factors, including genetic factors and an unhealthy lifestyle. Preventing and treating hypertension is very important in order to reduce risk factors for death. Prevention and treatment of hypertension with traditional medicine or herbal medicine is an alternative that is currently in great demand and attention because it has minimal side effects and is quite effective. Andrographis paniculata is a medicinal plant that has been widely studied and is effective in preventing and treating hypertension. The main content of this plant is andrographolidine which is a phytochemical substance which has many benefits, including antihypertension. Objective: The aim of this outreach activity is to provide understanding to the public about the use of bitter (Androghraphis paniculata) to prevent and treat hypertension. Method: Education to the public about the use of Androghraphis paniculata is carried out through the lecture method. The material presented is an explanation of hypertension, the benefits of bitter as a medicinal plant, the benefits of bitter in preventing and treating hypertension and how to process it on a household scale. Explanation of how to process bitter for treatment, namely using the infusion method. Giving pre-tests and post-tests to counseling participants is carried out to evaluate the level of community understanding. Result: By providing education about the use of bitter to prevent and treat hypertension, it can increase public knowledge about hypertension, the causal factors, as well as the benefits of bitter and how to use it as a medicinal plant. Knowledge before and after counseling increased by 36.65%. The community is very enthusiastic in following the outreach that we do. Conclusion: With the outreach, participants know more about hypertension and the use of bitter in preventing and treating hypertension and how to process it. Participants' knowledge increased by 36.65%.